Hepatic Epigenetic Reprogramming After Liver Resection in Offspring Alleviates the Effects of Maternal Obesity - Simino, Lais A. de Paula; Fontana, Marina Figueiredo; de Fante, Thais; Panzarin, Carolina; Ignacio-Souza, Letícia Martins; Milanski, Marciane; Torsoni, Marcio Alberto; Desai, Mina; Ross, Michael G.; Torsoni, Adriana Souza (Frontiers in Cell and Developmental Biology, 2022)
Obesity has become a public health problem in recent decades, and during pregnancy, it can lead to an increased risk of gestational complications and permanent changes in the offspring resulting from a process known as metabolic programming. The offspring of obese dams are at increased risk of developing non-alcoholic fatty liver disease (NAFLD), even in the absence of high-fat diet consumption. NAFLD is a chronic fatty liver disease that can progress to extremely severe conditions that require surgical intervention with the removal of the injured tissue. Liver regeneration is necessary to preserve organ function. A range of pathways is activated in the liver regeneration process, including the Hippo, TGFβ, and AMPK signaling pathways that are under epigenetic control. We investigated whether microRNA modulation in the liver of the offspring of obese dams would impact gene expression of Hippo, TGFβ, and AMPK pathways and tissue regeneration after partial hepatectomy (PHx). Female Swiss mice fed a standard chow or a high-fat diet (HFD) before and during pregnancy and lactation were mated with male control mice. The offspring from control (CT-O) and obese (HF-O) dams weaned to standard chow diet until day 56 were submitted to PHx surgery. Prior to the surgery, HF-O presented alterations in miR-122, miR-370, and Let-7a expression in the liver compared to CT-O, as previously shown, as well as in its target genes involved in liver regeneration. However, after the PHx (4 h or 48 h post-surgery), differences in gene expression between CT-O and HF-O were suppressed, as well as in microRNA expression in the liver. Furthermore, both CT-O and HF-O presented a similar regenerative capacity of the liver within 48 h after PHx. Our results suggest that survival and regenerative mechanisms induced by the partial hepatectomy may overcome the epigenetic changes in the liver of offspring programmed by maternal obesity.